Ad'iyah al-Anbiya' Fi al-Qur'an al-Karim (Dirasah Tahliliyah Ma'aniyah) - Itsnaini Muslimati Alwi (Arabiyatuna : Jurnal Bahasa Arab, 2019)
This study aims to describe and to determine the type of kalam in prophet supplications of al-Quran with its purpose. There are some verses in al-Quran containing prophet supplication. The type of this research is descriptive qualitative. The source of data is the verses of prophet supplication in the holy Quran. The finding of this research show that the theme of prophet supplications in al-Quran are 63 times in 26 surat and 74 verses in al-Quran. The type of kalam in prophet supplications in al-Quran are two kinds, they are kalam khabar and kalam insya. There are several purposes in each prophet supplication, the purpose of using kalam khabar are idzharu adh-dhafi wal khusyui, tahriiqu al-himmah ila maa yalzamu tahshiluhu, al-istirham wa al-istithaf, al-fakhru, at-tadzkir bima baina al-murotib min at-tafaawut, idzhaaru at-tahassur, idzhaaru at-tahassur ala syaiin mahbuub, al-hatstsu ala as-sayi wa al-jiddi, al-madah, and at-takhdzir. And the purpose of using kalam insya is ad-dua.